1989
DOI: 10.3109/02713688908997564
|View full text |Cite
|
Sign up to set email alerts
|

Cataract Prevention in Diabetic Octodon Degus with Pfizer's Sorbinil

Abstract: The Octodon degus has been reported to have higher aldose reductase activity in the lens compared to the gerbil and rat. When made diabetic the degus develop cataracts within 4 weeks. We have been able to completely prevent cataract formation in diabetic degus using Pfizer's sorbinil for up to 6 months. This is further evidence of the role of aldose reductase in the formation of cataracts in diabetes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
27
0
1

Year Published

1998
1998
2020
2020

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(29 citation statements)
references
References 2 publications
1
27
0
1
Order By: Relevance
“…This is in accord with literature reports in other rodents e.g. degus 7 , sand rats 31 , and in rats with streptozotocin induced diabetes 38 . Other etiologies are possible for cataract, such as inheritance, toxins or medication, injury of the lens or inflammation of the eye.…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…This is in accord with literature reports in other rodents e.g. degus 7 , sand rats 31 , and in rats with streptozotocin induced diabetes 38 . Other etiologies are possible for cataract, such as inheritance, toxins or medication, injury of the lens or inflammation of the eye.…”
Section: Discussionsupporting
confidence: 82%
“…4 Cataract formation in plains viscachas might be accelerated by an increased aldosereductase activity in the lens similar to degus with type 2 diabetes mellitus. 7 Diabetic cataract is always bilateral. In the animal with unilateral cataract, a trauma-related etiology was suspected.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Using this animal model and indirect ophthalmoscopy and portable slit lamp examination, we demonstrated that the ARI fidarestat, completely blocked slow-developing diabetic cataract formation. The important role of AR in diabetic cataractogenesis is in line with studies in other diabetic animal models including, i) the South American rodent, Octodon degus, which has a very high AR expression in the lens, and rapidly develops cataracts after spontaneously becoming diabetic in a laboratory environment (37,38), and ii) transgenic mice selectively expressing human AR in the lens, which, in contrast to wild-type diabetic mice that do not accumulate sorbitol in the lens and do not develop cataracts, display clearly manifest lens sorbitol accumulation and opacification (39).…”
Section: Discussionmentioning
confidence: 50%
“…This transgenic data is complemented by prevention studies with aldose reductase inhibitors. Administration of aldose reductase inhibitors at the onset of diabetes or galactosemia have been observed to result in dose dependent inhibition of sugar cataract formation in rats, Octodon degus and dogs (Kador and Kinoshita, 1984 ;Datiles and Fukui, 1989 ;Sato et al, 1998). Age-dependent studies also illustrate the importance of lenticular aldose reductase levels on sugar cataract formation.…”
Section: Discussionmentioning
confidence: 84%